2000
DOI: 10.1002/1096-9071(200009)62:1<82::aid-jmv12>3.0.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

GBV-C/HGV genotypes: Proposed nomenclature for genotypes 1-5

Abstract: The GB virus-C and hepatitis G virus (GBV-C/HGV) are variants of the same flavivirus. This proposal attempts to clarify the conflicting nomenclature for GBV-C/HGV genotypes. The first three genotypes described were genotype 1 (West Africa); genotype 2 (US/Europe) and genotype 3 (Asia). Subsequently, two groups published data from South Africa and Southeast Asia both stating the presence of a novel "4th genotype." These isolates are distinct phylogenetically. It is proposed that the nomenclature for genotypes 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 11 publications
(18 reference statements)
4
32
0
Order By: Relevance
“…These isolates, detected in blood donors and hepatitis patients, were designated by the authors as genotype 5-not to be confused with the novel isolates identified in South Africa in the previous year [Tucker et al, 1999] and designated subsequently genotype 5 [Tucker and Smuts, 2000]. An additional study [Mison et al, 2000] suggested the existence of a novel GBV-C genotype found among Pacific Islanders that was unlike genotype 1, 2, or 3 sequences.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…These isolates, detected in blood donors and hepatitis patients, were designated by the authors as genotype 5-not to be confused with the novel isolates identified in South Africa in the previous year [Tucker et al, 1999] and designated subsequently genotype 5 [Tucker and Smuts, 2000]. An additional study [Mison et al, 2000] suggested the existence of a novel GBV-C genotype found among Pacific Islanders that was unlike genotype 1, 2, or 3 sequences.…”
Section: Introductionmentioning
confidence: 95%
“…Other sequences from Indonesia identified as genotype 4 by Handajani et al grouped with sequences from Myanmar and Vietnam [Naito et al, 1999]. The latter constituted the fourth genotype reported and was subsequently selected as the prototypical genotype 4 isolates by Tucker and Smuts [2000] in their proposed GBV-C nomenclature. Handajani et al did not include the sequences reported in 1999 by Naito et al in their analysis and therefore appear to have identified the fourth GBV-C genotype independently, but sometime after, Naito et al Thus, the GBV-C isolates from Indonesia reported by Handajani et al included representatives of the genotype 4 clade previously described and also a new clade, genotype 6.…”
Section: Sequence Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatitis G virus (HGV, or GB virus C) is an enveloped positive-sense, single-stranded virus belonging to the family Flaviviridae (1). This virus is transmitted via blood and blood products, like the hepatitis C virus (HCV) (2).…”
Section: Introductionmentioning
confidence: 99%
“…There are geographically divergent isolates, with different genotypes predominating in West Africa, the United States/Europe, and Japan (Loureiro et al 2002, Pavesi 2001, Tucker & Smuts 2000. There is evidence that HGV was introduced from Asia to the New World by earlier humans migrating across the Bering Strait (Loureiro et al 2002).…”
Section: Hepatitis G Virusmentioning
confidence: 99%